Empowering science and mathematics for global competitiveness : proceedings of the Science and Mathematics International Conference (SMIC 2018), November 2-4, 2018, Jakarta, Indonesia - Science and Mathematics International Conference (2018 : Jakarta, Indonesia).; Rahmawati, Yuli; Taylor, Peter Charles (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
This conference proceedings focuses on enabling science and mathematics practitioners and citizens to respond to the pressing challenges of global competitiveness and sustainable development by transforming research and teaching of science and mathematics. The proceedings consist of 82 papers presented at the Science and Mathematics International Conference (SMIC) 2018, organised by the Faculty of Mathematics and Natural Sciences, Universitas Negeri Jakarta, Indonesia. The proceedings are organised in four parts: Science, Science Education, Mathematics, and Mathematics Education. The papers contribute to our understanding of important contemporary issues in science, especially nanotechnology, materials and environmental science; science education, in particular, environmental sustainability, STEM and STEAM education, 21st century skills, technology education, and green chemistry; and mathematics and its application in statistics, computer science, and mathematics education.
OCLC-licensed vendor bibliographic record.
Keywords: Research -- Congresses; Science -- Study and teaching -- Congresses; Mathematics -- Research -- Congresses; Mathematics -- Study and teaching -- Congresses; SCIENCE / Study & Teaching; MATHEMATICS / General; MATHEMATICS / Applied; TECHNOLOGY / Engineering / Civil